Studies on Efficiencies of Bio-gas Production in Anaerobic Digesters using Water Hyacinth and Night-soil Alone as well as in Combination - Kumar, Sunil (Asian Journal of Chemistry, 2016)
Water-hyacinth and nigh-soil alone as well as in combination with each other in various proportions (1 : 3 and 3 : 1) have tremendous potential to produce bio-gas (rich in methane content) through anaerobic digesters. The sludge obtained from mixed fed was improved in terms of nitrogen, phosphorus and potassium in comparison t hyacinth alone. The sludge can be utilized as a very good manure. The technology is very simple and can be easily implemented in rural areas to fulfill the energy crisis especially for cooking.